Continuous versus interrupted technique for repair of episiotomy - kellow, sundus yousif; kamel, salama; Al-ani, Hanaa; Wahab, Lalye Mohammad (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objectives: Some degree of perineal trauma following vaginal delivery is common and this may cause several maternal morbidity. This study is to evaluate the repair techniques of continuous versus interrupted methods for repair of episiotomy regarding consumption of suture material and cost, estimation of the pain at short term (2 and 6 weeks), necessity to take out the stitches, infection, dehiscence and dyspareunia. Methods: A total of 100 labouring women were divided into two groups; the first group (group A) includes 50 women their episiotomies were repaired with continuous, non locking suturing technique. The other group (group B) includes the other 50 women, their episiotomies were repaired with continuous, locking sutures of the vagina, interrupted sutures of the perineal muscles, and interrupted transcutaneous sutures of the perineal skin. The suture material used was the same in both groups (polyglactin 910). The women were observed for the first 12 hours in the hospital, and seen after two weeks and six weeks. Results: Significantly fewer women reported pain at two weeks postpartum with the continuous technique (96% mild pain and 4% moderate pain) while with interrupted technique 80% had mild pain, 14% moderate pain and 6% severe pain with a P-value of 0.039. Similar results were observed at 6 weeks postpartum, in favor of continuous technique in which no case was reported to have pain compared with 7 cases (14%) reported pain in interrupted group, with a P-value of 0.006. The rate of stitch removal was significantly lower for continuous group in comparison to interrupted group. Breast feeding also showed significant difference, being earlier in onset with the continuous group. Moreover, when the continuous technique was used for repair of all layers, there was a significant reduction in consumption of suture materials and cost. Conclusions|: This study have showed that perineal repair using continuous suturing technique is superior to interrupted technique by causing less maternal morbidity , early onset of breast feeding, less cost, also with better cosmetic acceptance.